Cerebral Palsy in Child Neurology and Neurodevelopmental Disabilities Training: An Unmet Need. (March 2022) - Wilson, Jenny L.; Kim, Young-Min; O'Malley, Jennifer A.; Gelineau-Morel, Rose; Gilbert, Laura; Bain, Jennifer M.; Aravamuthan, Bhooma R.
Background: Cerebral palsy (CP) is the most common cause of childhood motor disability. However, there is limited guidance on training of child neurologists and neurodevelopmental disability specialists in the care of individuals with cerebral palsy. We sought to determine training program directors' impressions of the importance and adequacy of training in the diagnosis and management of cerebral palsy. Methods: In this cross-sectional study, all 82 child neurology and neurodevelopmental disability program directors were asked to complete a survey querying program characteristics, aspects of training in cerebral palsy, importance of cerebral palsy training, and perceived competence at graduation in cerebral palsy care. Results: There were 35 responses (43% response rate). Nearly all program directors (91%) reported "learning to diagnose cerebral palsy" as very important, and most (71%) felt that "learning to manage cerebral palsy" was very important. Although most program directors reported trainees to be very or extremely competent in cerebral palsy diagnosis (77%), only 43% of program directors felt that trainees were very or extremely competent in cerebral palsy management. Time spent with cerebral palsy faculty was associated with higher reported competence in cerebral palsy diagnosis ( P  = .03) and management ( P  < .01). The presence of a cerebral palsy clinic was associated with higher reported competence in cerebral palsy management ( P  = .03). Conclusions: Child neurology and neurodevelopmental disability program directors reported that training in cerebral palsy is important for residents; however, a significant proportion felt that residents were not very well prepared to manage cerebral palsy. The development of cerebral palsy curricula and exposure to cerebral palsy clinics may improve training, translating to better care of individuals with cerebral palsy.